Identification and Validation Prognostic Impact of MiRNA-30a-5p in Lung Adenocarcinoma - Jiang, Xiulin; Yuan, Yixiao; Tang, Lin; Wang, Juan; Zhang, Dahang; Cho, William C.; Duan, Lincan (Frontiers in Oncology, 2022)
Background MiRNA-30a-5p is a microRNA found to be decreased in multiple human cancers, including non-small cell lung cancer (NSCLC). However, the potential molecular mechanisms of miRNA-30a-5p involve in the progression of NSCLC remains unclear. Methods Data were collected from the The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The starbase was utilized to examine the expression of miRNA-30a-5p, the kmplot and GEPIA databases were employed to analysis the tumor stage and prognosis of miRNA. We utilized the cluster Profiler package and GSEA software to analysis the potential signaling pathway and molecular function in NSCLC. We used a GSVA R package to examine the LUAD immune infiltration of 24 tumor-infiltrating immune cells in tumor samples through ssGSEA. Using qRT-PCR assay was conducted to detect the expression levels of miRNA-30a-5p in NSCLC cell lines and tissues. The function of miRNA-30a-5p on cell proliferation, cell migration and self-renewal were examine by the cell growth curve, clone information, transwell , wound healing assays and tumor-sphere assays. Results In this study, we investigated the role of miRNA-30a-5p in NSCLC and found that miRNA-30a-5p expression was significantly decreased in NSCLC cells lines, NSCLC cancerous tissues and peripheral blood serum, miRNA-30a-5p lower expression patients exhibit worse clinical outcome compared to the patients with higher miRNA-30a-5p expression, decreased expression of miRNA-30a-5p was associated with advanced clinical pathologic characteristics. Receiver operating characteristic (ROC) curve analysis of miRNA-30a-5p showed an area under the curve (AUC) value of 0.902, indicating its prognostic value in NSCLC. Moreover, immune infiltration and GSEA enrichment analysis demonstrated that miRNA-30a-5p expression was associated with oncogenic and immune cell infiltrated in NSCLC. Finally, we found that miRNA-30a-5p inhibits cell proliferation, migration and self-renewal abilities of NSCLC in vitro.